(untitled) (Indianapolis, Ind., 1997)
Inside Windows NT Server 4 RAS is a must-have resource, packed with professional tips, helpful hints, and expert advice for installing, configuring, and optimizing Remote Access Services. This comprehensive reference explores the use of RAS to its fullest potential. You'll master key features and concepts through hands-on, step-by-step procedures. Explore how to internetwork with RAS and master connectivity issues--such as using modems, ISDN, and X.25. Plus, find expert, detailed coverage on Steelhead/RRAS--the latest technology from Microsoft.
Keywords: Hệ điều hành Microsoft Windows NT,Microsoft Windows NT Server